Place of the Subaltern ‘Shudras’ in the Ancient Indian Knowledge Tradition (International Journal of Food and Nutritional Sciences, 2022)
India has always been known for its knowledge tradition and knowledge culture. IndianKnowledge Tradition has an influential and rich history since the ancient age. It has its owncharacteristics, its place of learning, its texts, and their classifications. In this knowledge traditionin ancient India knowledge was based on the Vedas and other Dharmashastras. Though it wasfamous for its disciplined education and great knowledge of all areas, it had some discrepancies.In ancient India, the knowledge system was based on caste hierarchies. Only the students fromthree upper castes like Brahmins, Kshatriyas, and Vaishyas had the right to enter the schools andtake education. They were dvijas (twice-born) and had the right to Upanayana, the initiatingceremony of schooling. The Shudras were not permitted to attain Upanayana because they werenot twice-born. They had no right to enter the schools or to read and recite the Vedas. TheShudras were oppressed, marginalized 'subalterns' and were living the lives of subordinatesunder the domination of higher castes. Although the term subaltern became regular with theemergence of 'Subaltern Studies' in the decade of 1980s, the subalterns have been in existencesince the beginning of human history. The Shudras were subalterns in ancient India and hadbeenkept away from education and knowledge. So it is needed to focus on the injustice done to thesubaltern Shudras in the Indian education system and knowledge in ancient India.